The ethics of medical research on humans - Foster-Gilbert, Claire, 1964- (Cambridge University Press, 2001)
This book examines the three main approaches to moral decision-making and looks at the problematic boundaries where best practice ends and experimentation begins. It provides a thorough, non-partisan grounding in what the ethical principles are and how they can be applied. It will be essential reading for all medical decision-makers.